Not everyone is a follower: The behaviour of interest rate and equity markets within major economies relative to the United States. (12th August 2020) - Tunaru, Diana; Fabozzi, Frank J.
Abstract: Using a multifactor continuous‐time model, we study the impact of the global financial crisis on the information transmission mechanism between interest rate and equity markets in the United States and each of the four major economies (United Kingdom, Japan, Germany and Canada). The exchange of information through the return channel shows that the equity markets communicate differently with the short‐ and long‐term interest rate markets: the linkages between the equity and money markets follow similar patterns across all four major economies, whereas the feedbacks between the returns on equity and bond markets suggest country‐specific relationships with the United States. The level of interdependence is higher between the equity and long‐term bond markets, whereas within the money markets context, there is evidence of the flight‐to‐quality phenomenon.